2015
DOI: 10.1111/iju.12901
|View full text |Cite
|
Sign up to set email alerts
|

Association between diabetes mellitus and oncological outcomes in bladder cancer patients undergoing radical cystectomy

Abstract: Among bladder cancer patients who underwent radical cystectomy, the diabetes mellitus patients had worse cancer-specific mortality and overall mortality outcomes than the non-diabetes mellitus patients. The mechanism of association between diabetes mellitus and urothelial bladder cancer should be investigated to validate the present results in a future prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Masaoka and his teammates (30) declared that smoking was a persuasive risk factor for BC in Japanese. Other factors such as obesity (31)(32)(33), and diabetes (34)(35)(36) were also considered to be related to the occurrence and development of BC. Coincidentally, these factors are highly recognized to be tightly associated with the risk of CVD, which could well explain the higher proportion of CVD mortality in UBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Masaoka and his teammates (30) declared that smoking was a persuasive risk factor for BC in Japanese. Other factors such as obesity (31)(32)(33), and diabetes (34)(35)(36) were also considered to be related to the occurrence and development of BC. Coincidentally, these factors are highly recognized to be tightly associated with the risk of CVD, which could well explain the higher proportion of CVD mortality in UBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…And we performed the full-text screening, we nally 5 studies in the present analysis. [8][9][10][11][12] The screening procedure was showed in the Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, our results found that those factors are underpowered to reveal any association with complications. Evidence that the risk of post-RARC complications is significantly higher in patients with DM, CKD, and dyslipidemia has been reviewed separately and individually in several literatures, [14][15][16][17][18][19][20] but our strength is considered to be the first to try to reveal an association in one study at once. Knorr et al 16 reported that chronic obstructive pulmonary disease (P = 0.030), CCI (P = 0.020), and Indiana pouch diversion (P = 0.002) were significant predictors of early complication.…”
Section: Discussionmentioning
confidence: 99%